2013
DOI: 10.1080/01635581.2013.828088
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Intake and Risk of Nasopharyngeal Carcinoma: A Case-Control Study

Abstract: Some studies examined the inverse relation between nasopharyngeal carcinoma (NPC) risk and dietary fibers in endemic populations. By means of a hospital-based case-control study, we verified whether this association was also present in Italy in connection with various types of dietary fibers. Cases were 198 patients with incident, histologically confirmed, NPC admitted to major teaching and general hospitals during 1992-2008. Controls were 594 patients admitted for acute, nonneoplastic conditions to the same h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…It has been concluded that insoluble fiber may provide slightly higher chemoprotection compared to soluble one [32]. In a large cohort study intakes of legumes, whole grains, and cruciferous vegetables were also associated with a 16% -18% reduced risk of renal cell carcinoma [33].…”
Section: Introduction To Different Types Of Dietary Fiber and Associmentioning
confidence: 99%
“…It has been concluded that insoluble fiber may provide slightly higher chemoprotection compared to soluble one [32]. In a large cohort study intakes of legumes, whole grains, and cruciferous vegetables were also associated with a 16% -18% reduced risk of renal cell carcinoma [33].…”
Section: Introduction To Different Types Of Dietary Fiber and Associmentioning
confidence: 99%
“…Previous results based on these data indicated an increased consumption of carotenoids, including α-carotene and β-carotene, and yellow- or red-pigmented vegetables to be protective against NPC [30,43]. In addition, dietary intake of soluble and insoluble fibers was inversely related to NPC risk [31]. All of these nutrients and food items contribute to decreased DII scores [13].…”
Section: Discussionmentioning
confidence: 95%
“…A case–control study on NPC was conducted between January 1992 and December 2008 within an established network of centres, including Aviano (Pordenone) and Milan in northern Italy, and Naples and Catania in southern Italy [31,30]. Cases were 198 European subjects (157 men, 41 women; median age 52 years, range 18–76 years) admitted to major teaching and general hospitals in the study areas with incident, histologically confirmed incident NPC diagnosed within one year before interview, and with no history of cancer at other sites.…”
Section: Methodsmentioning
confidence: 99%
“…Итальянским медикам удалось показать достоверную обратную связь потребления ПВ и риска развития карциномы носоглотки [25], который снижался на 42 % в группе с максимальным потреблением ПВ. Также достоверная обратная связь была ими установлена и с потреблением растворимых (пектин) и нерастворимых (клетчатка и лигнин) ПВ.…”
Section: Introductionunclassified